Scalable Compliance Payment Systems in Law Enforcement: Balancing Security, Efficiency, and Civil Liberties - Arpit Mittal (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The rapid evolution of digital payment systems has created unprecedented challenges for law enforcement agencies worldwide in monitoring and preventing financial crimes. This article examines the implementation of scalable compliance payment systems in law enforcement, analyzing their benefits, challenges, and implications for civil liberties. The article explores how emerging technologies such as artificial intelligence, machine learning, and blockchain have transformed compliance monitoring capabilities while introducing new security and privacy concerns. The article evaluates the effectiveness of automated compliance systems in fraud detection, regulatory reporting, and investigation capabilities while addressing critical challenges including privacy risks, resource constraints, and regulatory complexity. The findings suggest that successful implementation requires a balanced approach combining technological innovation with robust governance frameworks, emphasizing the importance of cross-industry collaboration and continuous system adaptation to emerging threats.